2020
DOI: 10.1080/2574254x.2020.1753472
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of eating and food preparation behaviours for urban private school students in India

Abstract: Introduction: Adolescents' perceptions of eating and culinary behaviours have important implications for their health and nutritional profiles. The purpose of the current investigation is to understand Indian adolescents' perceptions of healthy eating and meal preparation. Methods: Year nine students (n = 1026; 35% males) aged 14-16 years from nine English-speaking private secondary schools in Kolkata, India completed a paperbased, self-reported questionnaire which included questions about facilitators and bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 55 publications
(72 reference statements)
1
8
0
Order By: Relevance
“…These findings match those observed in previous studies conducted with children and adolescents in other populations which showed that the taste, smell, texture, appearance, as well as their emotional attachment to foods (e.g. pleasure and disgust) were more influential on their food choices than the nutritional value of food (10,11) . It has been suggested that at this age, the concept of nutrition and diet-related diseases may be too abstract to comprehend or perceived as distant and irrelevant (30) .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings match those observed in previous studies conducted with children and adolescents in other populations which showed that the taste, smell, texture, appearance, as well as their emotional attachment to foods (e.g. pleasure and disgust) were more influential on their food choices than the nutritional value of food (10,11) . It has been suggested that at this age, the concept of nutrition and diet-related diseases may be too abstract to comprehend or perceived as distant and irrelevant (30) .…”
Section: Discussionsupporting
confidence: 91%
“…To the best of our knowledge, this is the first study to examine children's perspectives of the influences on their dietary behaviour in Singapore. The use of qualitative methods with children directly allowed us to gather rich data from them through their perspectives, therefore contributing to the limited but growing body of literature in Asia (10,11) and locally (43,44) . However, there are some limitations to be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most adolescents either skip breakfast or have an unhealthy or inappropriate one [ 6 , 14 , 21 ]. Thus, educational strategies promoting healthy eating and for this age group are of key relevance, as habits acquired in childhood and adolescence are usually maintained in adulthood [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the average score of social support in female adolescents was 1.4-fold higher than in males, indicating the stronger social support provided by family, friends, etc., may strongly affect the adolescents' choice to diet [31,43]. A study in nine private secondary schools of urban India also found that over 60% of students (aged 14-16 years) thought their current F&V intakes are adequate [44], although previous research showed inadequate number of F&V intakes among many of these students [40]. Recent studies showed that parental support was associated with higher F&V consumption among Texas 8th-and 11th-grade students in USA [45] and 10th-and 12th-grade students in Dubai [46].…”
Section: Discussionmentioning
confidence: 99%